Sosialisasi Pembentukan Koperasi Swadaya Melalui Pemberdayaan Kelompok Wanita Tani (Kwt) Desa Rajaiyang Kabupaten Indramayu - Dian Tri Hapsari; Ana Kuswanti; Munadhil Abdul Muqsith; Radita Gora Tayibnapis; Hermina Manihuruk (IKRA-ITH ABDIMAS, 2023)
The Empowerment of Women Farmers Groups (KWT) encourages the formation of self-helpcooperatives. The hope is that the socialization of self-help cooperatives can be a means to helpease the economic burden that has been felt by farmers while waiting for the harvest to arrive.Farmers in Rajaiyang village usually depend on middlemen by borrowing money first, or byborrowing capital from moneylenders to meet their daily needs. A similar reality also occurs whenstarting the planting season. KWT and the Association of Farmers Groups (Gapoktan) inRajaiyang Village depend on moneylenders and middlemen, to meet their supply needs for seedsand fertilizers. This background makes Gapoktan and KWT the target of socializing the formationof self-help cooperatives accompanied by local village heads. It is hoped that the socialization ofthe formation of this self-supporting cooperative can be a pilot project for empowering womenfarmers in dealing with the very concerning problem of debt and credit. So that the existence ofcooperatives can help farmer groups financially in meeting their daily needs. In addition,socialization of the formation of self-help cooperatives among farmers is also expected to increaseagricultural productivity and economic independence of farmers in Rajaiyang village, IndramayuRegency.